Semantic communications for future: basic principle and implementation methodology - Ping ZHANG; Kai NIU; Shengshi YAO; Jincheng DAI (Tongxin xuebao)
The basic principle of semantic communications and the associated implementation methodology were introduced.First, the systematic model of semantic communications was proposed and basic concepts and terminology were deduced by comparing the fundamental differences between classic communications and semantic communications.Thus, the technological advantages of semantic communications were concluded.Then, the development of semantic information theory was retrospected and the measurement system of semantic information was established.Furthermore, the normalized conditional complexity (NCC) was proposed to evaluate the limit of semantic compression and the property of semantic typical sequence coding was discussed so as to reveal the corresponding asymptotic performance.In addition, the semantic coding transmission methods were classified into two typical schemes, that is, direct coding and transform coding, and the basic principles of these schemes were presented.For the text, speech, and image sources, the superior performance of the semantic coding techniques were demonstrated.Finally, the difficulty and open issues of the semantic communications were further concluded and further research directions were pointed out.